Zadanie 2. Rozwiąż równania. Rozwiązania wpisz poniżej.
a) – ( x + 3) + (2x – 1) = (1 + 4x) + (3+x)
b) – (x + 3) – (2x + 8 ) = (–3 – 2x) + (2x+1)
c) 3 (x–4) – 2 (2x–5) =– 4
d) – 2 (x+3) + 4 (2x + 3) = – 6​


Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

A) -x-3+2x-1=1+4x+3+x

-x+2x-4x-x=1+3+3+1

-4x=8/(-4)

x= -2

B) -x-3-2x-8= -3-2x+2x+1

-x-2x+2x-2x= -3+1+3+8

-3x=9/(-3)

x= -3

C) 3x-12-4x+10= -4

-x= -4+12-10

-x= -2/(-1)

x=2

D) -2x-6+8x+12= -6

6x= -6+6-12

6x= -12/6

x= -2

Odpowiedź:

a)   – ( x + 3) + (2x – 1) = (1 + 4x) + (3+x)

-x-3+2x-1=1+4x+3+x

-x+2x-4x-x=1+3+3+1

-4x=8 /-4

x=-2

b) – (x + 3) – (2x + 8 ) = (–3 – 2x) + (2x+1)

-x-3-2x-8=-3-2x+2x+1

-x-2x+2x-2x=-3+1+3+8

-3x=15 /-3

x=-5

c)  3 (x–4) – 2 (2x–5) =– 4

3x-12-4x+10=-4

3x-4x=-4+12-10

-x=-2  /-2

1/2x=1  /*2

x=2

d)  – 2 (x+3) + 4 (2x + 3) = – 6​

-2x-6+8x+12=-6

-2x+8x=-6+6-12

-6x=-12 /-6

x=2